2013
DOI: 10.1111/jai.12301
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on embryo survival and development in pallid sturgeon Scaphirhynchus albus (Forbes & Richardson 1905) and shovelnose sturgeon S. platorynchus (Rafinesque, 1820)

Abstract: Summary The thermal response of pallid sturgeon Scaphirhynchus albus and shovelnose sturgeon S. platorynchus embryos was determined at incubation temperatures from 8 to 26°C and 8 to 28°C, respectively. The upper and lower temperatures with 100% (LT100) embryo mortality were 8 and 26°C for pallid sturgeon and 8 and 28°C for shovelnose sturgeon. It was concluded that 12–24°C is the approximate thermal niche for embryos of both species. Generalized additive and additive‐mixed models were used to analyze survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…The results from this study indicate no significant difference in thermal tolerances between pallid and shovelnose sturgeon, implying that both species occupy a similar thermal niche early on in ontogeny. This result agrees with the notion that pallid and shovelnose sturgeon utilize the same thermal niche as embryos (Kappenman et al ., ). Temperature is a critical component in determining the metabolic energy demand (Hanson et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…The results from this study indicate no significant difference in thermal tolerances between pallid and shovelnose sturgeon, implying that both species occupy a similar thermal niche early on in ontogeny. This result agrees with the notion that pallid and shovelnose sturgeon utilize the same thermal niche as embryos (Kappenman et al ., ). Temperature is a critical component in determining the metabolic energy demand (Hanson et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments showed that larval pallid sturgeon have a greater tolerance for high water temperatures than newly fertilized pallid sturgeon embryos (Kappenman et al., ) and a similar upper thermal tolerance as juvenile Scaphirhynchus sturgeon (Kappenman et al., ; Hupfeld et al., ). Results from this experiment provide evidence that pallid sturgeon larvae acclimated to 22°C can withstand exposure to 28°C water for 7 days without a loss of equilibrium or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Extreme temperatures can lead to reduced metabolic function, delayed development, and direct mortality in fish (Harig and Fausch, 2002;Schultz and Bertrand, 2011). Alterations to thermal habitats have been identified as a mortality mechanism in Scaphirhynchus sturgeons (Kappenman et al, 2009(Kappenman et al, , 2013Phelps et al, 2010;Hupfeld et al, 2014). Anthropogenic alterations to rivers and tributaries in the Missouri-Mississippi River basin have created unnatural zones of cold and warm water that can act as ecological traps.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were collected on 19 and 20 June 2012 when water temperatures in the river were optimal for Pallid Sturgeon spawning and embryo survival (Kappenman et al 2013). Samples were emptied into an 18.9-L plastic container and dissolved oxygen (DO), temperature, pH, and unionized ammonia were measured using a YSI (Yellow Springs Instrument, Inc., Yellow Springs, OH) Professional Plus meter.…”
Section: Methodsmentioning
confidence: 99%
“…The transition zone habitat has been previously described by Thorton (1990). As in 2012, measurements were collected on 18 June when water temperatures in the river were optimal for Pallid Sturgeon spawning (Kappenman et al 2013). Transects within each habitat type were spaced approximately 1 km apart.…”
Section: Methodsmentioning
confidence: 99%